2019 2nd International Conference on Electrical Materials and Power Equipment (ICEMPE) 2019
DOI: 10.1109/icempe.2019.8727244
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Fumed Silica by Dry Silanization for PP-based Dielectric Nanocomposites

Abstract: Novel nanocomposites for dielectric applications based on a polypropylene (PP) blend filled with nanosilica are developed in the frame of the European 'GRIDABLE' project. A systematic study of the influence of surface modification of the nanosilica on the dielectric properties of the PP/silica blend was performed. The main goal of this investigation was to modify the chemical composition of the silica surface, which is expected to improve the charge trapping properties of the nanocomposites. For the modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Therefore, the influence of modified nanofillers having different surface polarities on the charge trapping properties of the dielectric materials is studied. Previously, the introduction of different polar functional groups on the silica surface resulted in significant differences in charge trapping properties of the nanocomposites [13], [14]. Following up our previous study [14], the current research not only covers the phenomenon of charge trapping properties, but also includes various characterization methods to investigate the mechanism of it.…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, the influence of modified nanofillers having different surface polarities on the charge trapping properties of the dielectric materials is studied. Previously, the introduction of different polar functional groups on the silica surface resulted in significant differences in charge trapping properties of the nanocomposites [13], [14]. Following up our previous study [14], the current research not only covers the phenomenon of charge trapping properties, but also includes various characterization methods to investigate the mechanism of it.…”
Section: Introductionmentioning
confidence: 92%
“…This can be achieved, e.g., by the introduction of polar functional groups at the interface. 23,24 Siddabattuni et al 25 investigated epoxy nanocomposites with TiO 2 and BaTiO 3 nanoparticles, and observed that upon introduction of electron-withdrawing phenyl groups at the polymer−particle interface, the leakage current and dielectric loss was significantly reduced. This also led to an improvement in the dielectric breakdown strength.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the thermal stability of the adsorbent, TGA was performed in the temperature range of 20–600 °C as shown in Figure 1 c. The TGA profile shows two different regions of loss. According to the literature, the first loss (≈7%) occurs in the temperature range of 20–235 °C, which is mainly related to the loss of moisture content within the sample and some other gases that may be adsorbed on the surface due to improper storage such as CO 2 [ 37 ]. The other region extends in the temperature range of 235–600 °C and resulted in a 30% loss of the sample.…”
Section: Resultsmentioning
confidence: 99%
“…The other region extends in the temperature range of 235–600 °C and resulted in a 30% loss of the sample. This loss is mainly related to the dissociation of amino groups attached to the surface [ 37 ]. The mass loss of bare silica nanoparticles is 18%, while the total loss for S-DA is 37%.…”
Section: Resultsmentioning
confidence: 99%